2014
DOI: 10.1007/s00464-014-3560-4
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative outcomes of laparoscopic and robot-assisted major hepatectomies: an Italian multi-institutional comparative study

Abstract: This retrospective multi-institution study confirms that selected patients can safely undergo minimally invasive major hepatectomy, either LMH or RMH. The fact that intermittent pedicle occlusion could be avoided in RMH suggests improved surgical ability to deal with bleeding during liver transection, but further studies are needed before any final conclusion can be drawn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
123
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(135 citation statements)
references
References 35 publications
8
123
0
3
Order By: Relevance
“…A case report of robotic left hepatectomy with revision hepaticojejunostomy has also been published by Chen et al (43). Spampinato et al also included a case of extended right hemihepatectomy and Ji et al described one case of left hemihepatectomy with caudate lobe resection (25,41). Specific results regarding these individual cases have not been reported since they are part of the larger series previously described in this review.…”
Section: Major Hepatectomiesmentioning
confidence: 89%
See 1 more Smart Citation
“…A case report of robotic left hepatectomy with revision hepaticojejunostomy has also been published by Chen et al (43). Spampinato et al also included a case of extended right hemihepatectomy and Ji et al described one case of left hemihepatectomy with caudate lobe resection (25,41). Specific results regarding these individual cases have not been reported since they are part of the larger series previously described in this review.…”
Section: Major Hepatectomiesmentioning
confidence: 89%
“…Robotic surgery has the potential to overcome some of the limits of laparoscopy and, in past years, its range of applications in this field has quickly expanded. Major hepatectomies, extended right, extended left, posterior segments and living donor hepatectomies have been described in the literature (4,20,25,38,41,43,45,46). Perioperative and postoperative outcomes, as well as oncologic efficacy, are not inferior to open or laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Robotic MIS hepatectomy as a field is moving past its infancy. Nota et al (12) recently reported a collected series analysis of the 12 best studies up to 2015 (7,8,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). There is no doubt that hemi-hepatectomies can be performed with safety by the robotically-assisted approach (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Most data were obtained from prospectively maintained databases. Tables 3 and 4 showed the results of nonrandomized comparative studies comparing robotic and laparoscopic partial hepatectomy in patients with minor hepatectomies [18][19][20][21][22][23][24][25] and in patients with minor and major hepatectomies [26][27][28][29] . Although the perioperative outcomes seemed to be similar in both groups, the benefit of robotic approach has been shown in several studies.…”
Section: Robotic Vs Conventional Laparoscopic Partial Hepatectomymentioning
confidence: 99%